Pengaruh Senam Kaki Terhadap Kadar Glukosa Darah Pada Pasien Diabetes Melitus Tipe II : Literature Review - Qosymah , Mujjahidah Nuha; Panma, Yuanita (Neolectura, 2025)
Type II diabetes mellitus (DM) is a chronic disease characterized by hyperglycemia resulting from insulin resistance. One effective and simple non-pharmacological intervention is foot exercise as part of aerobic activity, which aims to improve blood circulation and insulin sensitivity. This study aims to examine the effect of foot exercise on blood glucose levels in patients with type II diabetes mellitus and to provide a critical review of its effectiveness. The research method employed a literature review approach of three articles obtained through a systematic search using Google Scholar based on specific inclusion and exclusion criteria. The findings indicate that all three studies reported foot exercise to be effective in reducing blood glucose levels in patients with type II diabetes mellitus. Therefore, it can be concluded that foot exercise has a significant effect on lowering blood glucose levels in patients with type II diabetes mellitus. Future studies are expected to further develop this research by expanding the study population and varying the duration and frequency of foot exercise.